Academic ecosystem as a key factor for developing regional AIC - Fikhtner Oxana; Petrova Anna (BIO Web of Conferences)
Agriculture is one of the priorities of economic development of any region, any country, as it is largely associated with ensuring national sovereignty and strategic security. Therefore, the development of agro- industrial complex is an important governmental task, which has its own methods and tools applied in each specific territory in accordance with its geographical location, resource potential and the needs of the population. Modern dynamics of economic development is characterized by rapidity and global instability, which requires deliberate and balanced decisions, the adoption of which is impossible without fundamental scientific knowledge. It is the scientific support of strategic management decisions in the AIC that will make it possible to achieve a high level of development of the industry, increase its competitiveness in the world market, and form a highly qualified human resources potential. The authors have attempted to conceptualize the possibilities of scientific support for the development of agro-industrial complex of the Russian region (Novgorod Region) using the ecosystem approach. The use of ecosystem approach principles allows finding complex solutions in the context of global socio-economic and technological challenges of our time. The experience of Yaroslav-the-Wise Novgorod State University is used as an example of best practices for the implementation of sci-tech and organizational and technological transformation of the regional agro-industrial complex, growth of product quality, full-time personnel, and living standards of citizens. The scientific and educational ecosystem of the regional AIC development predetermined the formation of a customer-oriented approach, sustainable business relations between individual participants of this market segment, increasing the level of manageability and state regulation of the industry, the introduction of digital platform solutions and the growth of efficiency of agriculture and related industries.